Female genital plastic and cosmetic surgery - Goodman, Michael (Michael P.), 1943- (Chichester, West Sussex, UK ; Hoboken, NJ : Wiley, 2016)
Female genital plastic surgery has become an increasingly sought-after option for women seeking 'improvement' in genital appearance, relief from discomfort, and increased sexual pleasure. These surgeries are a combination of gynecologic, plastic, and cosmetic procedures. Every year sees a higher demand for physicians properly trained and able to perform them. This unique text from the acknowledged experts in the field covers; - the anatomy of the area - the specific surgical procedures and all their variations - patients' rationales for surgery - training guidelines and ethical issues - outcome statistics - sexual issues - patient selection - potential risks and complications. Examining the issues from individual patient's perspectives, it is written in an academic but easy-to-read style with understandable and unambiguous drawings and photographs. It contains a step-by-step surgical approach, how to best select the right surgical candidates, how to treat this select group of patients, the sexual issues involved, how to individualize techniques for each specific patient, how to deal with criticism from colleagues or journalists, psychosexual issues, and patient protection.
Genital plastics : the history of development / Michael P. Goodman, with contributions from David Matlock -- Anatomic considerations / Orawee Chinthakanan, Robert D. Moore, John R. Miklos -- Definitions / Michael P. Goodman -- Philosophy, rationale, and patient selection / Michael P. Goodman -- Ethical considerations of female genital plastic/cosmetic surgery / Andrew T. Goldstein, Sarah L. Jutrzonka -- Patient protection and pre-operative assessment / Michael P. Goodman -- Surgical procedures I : vulva and mons pubis / Michael P. Goodman, with contributions from David Matlock, Alex Simopoulos, Bernard W. Stern, Otto J. Placik -- Surgical procedures II : perineoplasty, vaginoplasty, colpoperineoplasty ("vaginal rejuvenation") / Robert D. Moore, John R. Miklos, Orawee Chinthakanan -- The biomechanics and physiology of clitoral and vaginally activated orgasm : impact of vaginal tightening operations / Michael P. Goodman -- The G-spot / Dudley Robinson, Linda Cardozo -- Post-operative care / Michael P. Goodman -- Aesthetic male-to-female transsexual surgery / Marci Bowers -- Anesthetic choices and office based surgery / Michael P. Goodman -- Non-surgical cosmetic vulvo-vaginal procedures / Gustavo Leibaschoff, Pablo Gonzalez Isaza -- Surgical risks and untoward outcomes / Otto J. Placik -- Revisions and re-operations / Michael P. Goodman -- Psychosexual issues / Michael P. Goodman -- Outcomes / Michael P. Goodman -- Pearls for practice / Michael P. Goodman -- Standards of care / Michael P. Goodman.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Vagina -- Surgery; Vulva -- Surgery; Surgery, Plastic; Generative organs, Female -- Surgery; MEDICAL / Gynecology & Obstetrics; Generative organs, Female -- Surgery; Surgery, Plastic; Vagina -- Surgery; Vulva -- Surgery; Medical; Vulva -- surgery; Clinical Competence; Cosmetic Techniques; Gynecologic Surgical Procedures; Vagina -- surgery; Electronic books